2017
DOI: 10.1089/jmf.2016.3911
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ2 C1431T Polymorphism Interacts with the Antiobesogenic Effects of Kochujang, a Korean Fermented, Soybean-Based Red Pepper Paste, in Overweight/Obese Subjects: A 12-Week, Double-Blind Randomized Clinical Trial

Abstract: Kochujang, a Korean fermented soybean-based red pepper paste, has been reported to have beneficial health effects. The aim of this study was to examine the antiobesity effects of Kochujang as a supplement in overweight/obese subjects according polymorphisms in the obesity-linked gene, peroxisome proliferator activator receptor γ (PPARγ2). Sixty overweight/obese subjects, who had body mass indexes (BMI, kg/m) ≥23 or waist/hip ratios (WHR) ≥0.90 for males or ≥0.85 for females, were randomly assigned to either ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 34 publications
0
47
0
Order By: Relevance
“…In addition to genes, we must also consider the microbiome, which is a key component of precision medicine. Understanding how host-microbe associations are maintained in populations will help reveal individualized host-microbiome encoded disease phenotypes that can be integrated with multi-omics data sets to enhance precision medicine [74]. If metabolism changes and persists depending on human gene expression or intestinal microbes, the causal relationship leading to the disease can be understood using bioinformatics.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to genes, we must also consider the microbiome, which is a key component of precision medicine. Understanding how host-microbe associations are maintained in populations will help reveal individualized host-microbiome encoded disease phenotypes that can be integrated with multi-omics data sets to enhance precision medicine [74]. If metabolism changes and persists depending on human gene expression or intestinal microbes, the causal relationship leading to the disease can be understood using bioinformatics.…”
Section: Resultsmentioning
confidence: 99%
“…For example, kimchi consumption improved fasting blood glucose and other metabolic syndrome symptoms in overweight and obese adults (Kim et al, 2011), and similar improvements were observed in healthy adults (Choi et al, 2013). Consumption of a fermented soybean paste also improved plasma triglyceride levels in obese adults (Lee Y. et al, 2017). Perhaps the strongest evidence is for yogurt and improved lactose tolerance, due to in vivo expression and release of β-galactosidase by the yogurt culture microbes, S. thermophilus and L. delbrueckii subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Various secondary metabolites with biological properties are generated by enzymatic degradation of the raw ingredients of gochujang via microbes in the fermentation process (Jang et al, ; Lee, Lee, et al, ; Lee, Shin, et al, ; Lee et al, ; Shin et al, ). Koji used in gochujang production comprises cooked grains and/or soybeans that have been inoculated with a fermentation culture, the filamentous fungus Aspergillus oryzae.…”
Section: Introductionmentioning
confidence: 99%